Antibiotic enhanced dopamine polymerization for engineering antifouling and antimicrobial membranes - Zhao, Shuaifei; Golestani, Maryam; Penesyan, Anahit; Deng, Baolin; Zheng, Chunmiao; Strezov, Vladimir (Chinese chemical letters, 2020)
Membranes with excellent antifouling and antimicrobial properties were developed using a novel antibiotic-dopamine coating system. [Display omitted] In this work, we adopt a new tobramycin (TOB)-dopamine coating system to endow thin film composite membranes with excellent antifouling and antimicrobial properties. Combining the hydrophilic and antibiofouling properties of both TOB and polydopamine, the TOB-dopamine modified membrane exhibits improved antifouling and antimicrobial properties compared with the conventional dopamine modified and unmodified membranes. The TOB-dopamine system has two advantages over the conventional modification with dopamine and tris buffer solution. First, TOB-dopamine modification is more efficient than the conventional dopamine modification due to the accelerating effect of TOB on dopamine polymerization. Second, the TOB-dopamine modified membranes exhibit better hydrophilicity, and enhanced antifouling and antimicrobial properties than the conventional dopamine modified membrane. Beyond engineering membranes, the proposed TOB-dopamine system can also be extended for wider surface hydrophilic and antimicrobial modifications.